Analysis of Problem Solving Skills and Students Scientific Attitudes through the Implementation of Problem Based Learning Module - Arini, Affita Nur; Hartono, Hartono; Khumaedi, Khumaedi (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
The purpose of this study was to describe the physics problem solving skills and scientific attitudes of students after applying the Problem Based Learning (PBL) module, obtaining a valid and practical PBL devices and modules, knowing whether the application of PBL learning modules has an effective to improve physics problem solving skills and students scientific attitudes and to know the students response to the application of PBL learning modules. This study uses research on concurrent embedded design combinations, which is a combination research that combines two types of research namely quantitative and qualitative. The sample in this study was selected one class as an experimental class which was treated with PBL learning with PBL modules. Then 6 students were chosen from the experimental class to conduct more in-depth observations about problem solving  skills and scientific attitudes. After the application of PBL learning modules, physics problem solving skills and scientific attitudes of students have increased. PBL learning modules are valid and practical. The application of PBL learning modules has effective to improve physics problem solving skills and scientific attitudes of students. There were 88.24% of students giving positive responses and interested in participating in learning activities using PBL learning modules.